Algebra 1

Published by Prentice Hall
ISBN 10: 0133500403
ISBN 13: 978-0-13350-040-0

Chapter 8 - Polynomials and Factoring - 8-6 Factoring ax(squared) + bx + c - Mixed Review - Page 510: 65



Work Step by Step

In order to simplify $(q-15)^{2}$ we must apply the rule that states that $(a+b)^{2}$=$a^{2}$-2ab+$b^{2}$, and we'll set a=q and b=15. Therefore, $(q-15)^{2}$=$q^{2}$-2(q)(15)+$15^{2}$ =$q^{2}$-30q+225
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.